Neurobehcet pediátrico. Presentación de un caso y revisión de la literatura. - Visaga, Maribel (2013)
The first peruvian pediatric case of Neuro-Behcet, who had seizures, hemiparesis and a magneic nuclear resonance with a pseudotumoral imagine is here presented